Study of the piezoionic effect and influence of electrolyte in conducting polymer based soft strain sensors. Issue 4 (11th December 2019) - Woehling, Vincent; Nguyen, Giao T M; Plesse, Cedric; Petel, Yael; Dobashi, Yuta; Madden, John D W; Michal, Carl A; Vidal, Frederic
Abstract: Electronic conducting polymers (ECP) have been widely studied in a tri-layer configuration as soft, bending actuators. These electroactive materials have also been reported to behave as mechanical strain sensors able to convert mechanical stimulation into electrical signals. This sensing behavior is attributed to the so-called piezoionic effect and is observed and reported in most ionic electroactive polymers (EAPs). However, ambiguities remain on the origin of this effect, being attributed either to stress gradient induced ion motion or to Donnan potentials arising at the ECP/electrolyte interface. In this work, the sensor mechanism of trilayer ECP actuators is studied and discussed as a function of different physical and chemical parameters thanks to the versatile synthesis of conducting interpenetrating polymer networks. Results demonstrate that the main mechanism relies on stress gradient, as in other ionic EAPs, instead of Donnan potential. Moreover, a deep investigation of the electrolyte nature and its concentration is performed. Mobile ions deduced from actuation experiments are correlated with the sign of voltage output during sensing experiments. An interesting inversion point is demonstrated at a concentration of 2.5 M of 1-ethyl-3-methylimidazolium bis(trifluoromethyl-sulfonyl)imide in propylene carbonate where simultaneous charge compensation (no sensing) and volume compensation (no actuation) occur for mobile cations and anions, while electrochemical behavior remains unchanged.